Behavioral Model of Social Media Analytics Use in Public Relations - Anisa Diniati; Martha Tri Lestari; Purnama Alamsyah; Mia Damayanti; Raditya Pratama Putra (Mediator: Jurnal Komunikasi, 2025)
This study explores the use of Social Media Analytics (SMA) among public sector Public Relations (PR) officers in West Java, Indonesia, using the Theory of Planned Behavior (TPB) framework. A survey of 23 PR civil servants investigates how attitudes, subjective norms, perceived behavioral control, and behavioral intentions affect SMA adoption. Descriptive and Spearman correlation analyses reveal significant relationships, especially between perceived behavioral control and usage intention. PR officers generally display positive attitudes toward SMA but lack sufficient knowledge and technical skills. The study recommends training to enhance SMA proficiency and integration into PR functions. The research contributes a novel behavioral model explaining SMA adoption, extending TPB to the context of government digital communication. The findings underscore the strategic role of SMA in improving organizational communication, transparency, and public engagement. This study provides theoretical advancement by contextualizing TPB within public communication and practical guidance for policymakers and PR professionals seeking to optimize digital engagement strategies in developing countries.